2002
DOI: 10.1007/s00203-002-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology and biochemistry of ammonia oxidation by Nitrosomonas europaea

Abstract: Nitrosomonas europaea uses only NH(3), CO(2) and mineral salts for growth and as such it is an obligate chemo-lithoautotroph. The oxidation of NH(3) is a two-step process catalyzed by ammonia monooxygenase (AMO) and hydroxylamine oxidoreductase (HAO). AMO catalyzes the oxidation of NH(3) to NH(2)OH and HAO catalyzes the oxidation of NH(2)OH to NO(2)(-). AMO is a membrane-bound enzyme composed of three subunits. HAO is located in the periplasm and is a homotrimer with each subunit containing eight c-type hemes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
242
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(247 citation statements)
references
References 49 publications
5
242
0
Order By: Relevance
“…Figure 5a indicated that NH 2 OH 45 mg l À 1 completely inhibited phenol degradation, whereas 50 mg l À 1 NO 2 À did not inhibit phenol degradation. Both ammonia-oxidising Archaea and ammonia-oxidising Bacteria oxidise NH 3 into NH 2 OH (Arp et al, 2002;Vajrala et al, 2013), which is then further oxidised to nitrite (NO 2 À ) and finally nitrate (NO 3 À ). The experimental data clearly indicated that it was NH 2 OH, but not NO 2 À , NO 3 À or NH 3 , that inhibited phenol degradation in the coking wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5a indicated that NH 2 OH 45 mg l À 1 completely inhibited phenol degradation, whereas 50 mg l À 1 NO 2 À did not inhibit phenol degradation. Both ammonia-oxidising Archaea and ammonia-oxidising Bacteria oxidise NH 3 into NH 2 OH (Arp et al, 2002;Vajrala et al, 2013), which is then further oxidised to nitrite (NO 2 À ) and finally nitrate (NO 3 À ). The experimental data clearly indicated that it was NH 2 OH, but not NO 2 À , NO 3 À or NH 3 , that inhibited phenol degradation in the coking wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established that marine and terrestrial representatives of an abundant group of archaea, now classified as Thaumarchaeota, are autotrophic NH 3 oxidizers (1)(2)(3)(4)(5). Despite increasing evidence that ammonia-oxidizing archaea (AOA) generally outnumber ammonia-oxidizing bacteria (AOB), and likely nitrify in most natural environments, very little is known about their physiology or supporting biochemistry (6,7). Genome sequence analyses have pointed to a unique pathway for NH 3 oxidation, likely using copper as a major redox active metal, and coupled to a variant of the hydroxypropionate/ hydroxybutyrate cycle (8).…”
mentioning
confidence: 99%
“…NH 2 OH is subsequently oxidized to NO 2 − by the hydroxylamine oxidoreductase (HAO) (7), a heme-rich enzyme encoded by the hao gene (7). Of the four electrons released from the oxidation of NH 2 OH to NO 2 − , two are transferred to the terminal oxidase for respiratory purposes and two are transferred to AMO for further oxidation of NH 3 (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the different groups of AOAs prefer environments with different amounts of ammonium, e.g., open ocean, marine water columns, where typical ammonium concentrations are <0.03~1 μM (Konneke et al, 2005;Wuchter et al, 2006;, Beman et al, 2008) are dominated by Group 1.1a, while Group 1.1b are found in many Nrich environments, e.g., bioreactors and agricultural soils. Furthermore, increased amoA expression by AOAs has been found in soils after addition of 10 mM NH 4 Cl (Treusch et al, 2005) suggesting the expression of archaeal amoA gene, like bacterial amoA genes (Arp et al, 2002), may be induced by ammonia. Since agricultural soils and estuaries receiving agricultural run-off typically are usually reported to be higher ammonium concentrations, the ammoniaoxidizing archaea in group 1.1b lineage may have adapted to such environments, while the group 1.1a thrives in marine or oligotrophic ecosystems.…”
Section: Ammonia Oxidizing Crenarchaeotamentioning
confidence: 98%